Investor relations and investment efficiency - Godsell, David; Jung, Boochun; Mescall, Devan (Contemporary Accounting Research, 2023)
Abstract A rich literature suggests that investor relations officers (IROs) fulfill a one‐way information intermediary role by transmitting firm information to investors. We advance this literature with empirical evidence suggesting IROs are two‐way information intermediaries who also return investment efficiency‐increasing investor feedback to firm insiders. Exploiting granular investor relations activity data for 1,375 global firms, we document that firm investment efficiency is higher when IROs spend more time with existing institutional investors, conduct more institutional investor outreach, and meet more often with investment professionals (market intelligence collection), and when IROs transmit investment community feedback to board directors (market intelligence circulation). We mitigate endogeneity concerns stemming from our association tests by employing an expansive suite of control variables, a high‐dimensional fixed‐effects structure, an entropy‐balanced estimation sample, and an instrumental variables analysis. Our evidence supports theory predicting that managers learn about investment opportunities and their costs and benefits from investors and informs a literature predominantly characterizing IROs as one‐way information intermediaries.